Zero-days last for years. Issue 3 (March 2017) - Unknown
Abstract : A new study from the RAND Corporation, based on data about zero-day vulnerabilities, concludes that the average life expectancy for one of these bugs before it is publicly disclosed and patched is 6.9 years. Only a quarter of them survive for less than 18 months.